Pandangan terhadap Anak dalam Ajaran Islam - Nurcahyono, Moh. Lutfi (Taallum: Jurnal Pendidikan Islam, 2013)
Children in a family like banana trees, which bear fruit only once. Through its fruit, banana tree not only can grow up with dignity but also can be affected by disease; withered, thin, and then die with no edible fruit. So are children in a family, they could make their family proud, or they could fall into the darkness and obscurity. Based on this disturbing phenomenon, Islam encourages family as much and as early as possible to direct the development of children so as to grow up with dignity in the world and the hereafter.